TOTAL NUMBER: A BRIEF REVIEW OF ITS IMPORTANCE AND ITS USE IN ASSESSING CEREBELLAR DAMAGE IN THE RAT FOLLOWING EARLY POSTNATAL ALCOHOL EXPOSURE - Napper, Ruth MA (Image Analysis and Stereology, 2011)
Knowledge of the total number of structural components that make up the various neural networks within the central nervous system is fundamental to our understanding of its normal function and of dysfunction that may accompany injury and disease. This paper briefly reviews the methodology currently used to estimate number and discusses the importance of unbiased estimates of total number in determining changes in brain structure that may underlie dysfunction. An example from the olfactory bulb is used to demonstrate the potential invalidity of using estimates of total number of objects per single section. Exposure to alcohol during the early postnatal period results in motor dysfunction in adult rats. This paper presents data on the extent and magnitude of cell loss within the cerebellar network of the rat following alcohol exposure during postnatal days 4 to 9. High transient blood alcohol concentrations result in a Purkinje cell of 27% across the entire cerebellum but with regional variabiltiy, vermal lobule X has a 43% Purkinje cell deficit. This alcohol regimen also results in a neuronal loss of 28% and 25% within the deep cerebellar nucleus and inferior olivary nucleus respectively. Consistency of overall neuronal loss across diverse neuronal populations within the cerebellar network is discussed in the context of the maintenance of cerebellar connectivity.